Role of Itinerancy Among Attractors as Dynamical Map in Distributed Coding Scheme - Hoshino, Osamu; Usuba, Noriaki; Kashimori, Yoshiki; Kambara, Takeshi (Neural networks, 1997)
A basic frame, based on which certain features of sensory stimuli can be extracted systematically in a distributed coding scheme, has not been clarified yet. This paper proposes that the basic frame can be a dynamical map represented by itinerancy among attractors. Features of entities are encoded by attractors of neural networks. Relations between the features in each modality are mapped on dynamical links between the attractors in each network relevant to each modality. The itinerant states, in which the network dynamic state itinerates chaotically or cyclically among the attractors, can work as dynamical maps. The recognition of features is carried out by a phase transition from an itinerant state to a constituent attractor. The phase transition is induced by a short-term synaptic change based on the Hebbian rule under application of a relevant stimulation. A theta-like global oscillation is necessary for self-organized formation of the chaotically itinerant state.